Venta y distribución de flores exóticas por medio de comercio electrónico a nivel Internacional (2021)
In the following article, an analysis of the possibilities of the implementation of E-commerce in the sale of exotic flowers at an international level was carried out, taking into account the growth of this tool around the world and demonstrating its importance for the survival of the current and new companies. This is a useful tool for the penetration of new markets, new niches and the discovery of new clients from anywhere in the world.